Gender matters and the challenge for improving community health and well-being. Issue 2 (2nd April 2020) - Migliorini, Laura; Rania, Nadia; De Piccoli, Norma
Abstract: The present paper introduces present issue focused on community gender perspective and health in an Italian context. After a brief analysis of the disparity and inequity that persist in Europe and Italy, we present six papers from different Italian regions that demonstrate different elements of the complex gender matters and challenges of well-being and health in the community. Considering the differences in social vulnerability and risk between men and women, the unequal power relationships between the sexes could improve the efficacy of intervention and preventative actions. Through this series of papers, we aim to contribute to the debate about how gender perspective can shape studies and interventions that promote both individual and community health and well-being. Gender, one of the key determinants of health, is revealed in many ways; it is necessary to better understand and plan health service interventions to improve the health of women and men. Furthermore, more attention and reflection are needed to promote policy interventions for health and to consider the contribution of women to the health of the community.